ANALISIS FAKTOR KEBERHASILAN PROGRAM KELOMPOK USAHA BERSAMA: STUDI KASUS DI DESA PATUMBAK - Ardhansyah Putra Hrp; Dwi Saraswati (Universitas Medan Area, 2020)
This study aims to analyze the factors of determine success KUBE program in Patumbak Village. The research sample was determined by purposive sampling with the consideration that KUBE who eligible to be a sample, namely KUBE which was still active which was formed in 2010 to 2019. The methodology in this study used validity and reliability tests which also used multiple linear regression analysis. This study tested each variable with hypothesis testing and the coefficient of determination.The results of study are indicate that the success factors for KUBE are venture capital, ecperience entrepreneurship and saving loan business not have a significant effect on the success KUBE program.The Joint Business Group (KUBE) is a business group fostered by the Indonesian Ministry of Social Affairs which is formed several assisted families to carry out Productive Economic Entreprises (UEP) and Social Welfare Entreprise (UKS) to improving welfare for the community. The success of KUBE will make a big contribution for the government in achieving of reduce the poverty rate.